Relationship between tooth brushing maintenance actions and OHIS status in schizophrenia patients at Aceh Mental Hospital - Nufus, Fakhrul; Reca, Reca (Journal of Health Science and Medical Therapy, 2024)
Patients with schizophrenia often neglect their oral and dental hygiene, resulting in poor oral health status. Tooth brushing as a maintenance practice is one of the efforts to improve oral hygiene in patients with schizophrenia. The purpose of this study was to determine the relationship between tooth brushing maintenance practices and OHIS (Oral Hygiene Index Simplified) status in patients with schizophrenia at the Aceh Mental Hospital. This study used a cross-sectional design. The sample consisted of 60 schizophrenia patients at the Aceh Mental Hospital, selected using proportional random sampling technique. Data on tooth brushing maintenance practices were collected through a questionnaire, while OHIS status data were obtained through clinical examination. Data analysis used the chi-square test. The statistical test results showed a p-value of 0.013, which means the p-value < 0.05, so there is a significant relationship between tooth brushing practices and OHI-S status in schizophrenia patients at the Aceh Mental Hospital.